Digital Management of Online Student Admission (PPDB) in Islamic Early Childhood Education: A Case Study - Norhikmah Norhikmah; Musyarapah Musyarapah; Emine Yildiz (Indonesian Journal of Early Childhood Educational Research (IJECER), 2026)
The digital transformation of Islamic early childhood education requires adaptive, transparent, and ethical student admission management. This study aims to analyze the management of online student admission in Islamic early childhood education within the framework of digital transformation and Islamic educational values. A qualitative case study approach was employed, using in-depth interviews, non-participant observation, and institutional documentation. Data were analyzed through Miles and Huberman’s interactive model and interpreted using Islamic management principles, including amanah, ‘adl, shidq, mas’uliyyah, and khidmah. nThe findings indicate that online admission management enhances administrative efficiency, data organization, transparency, and reporting accuracy through structured digital planning and implementation. The process includes collaborative decision-making, digital registration systems, and developmental screening mechanisms. Key challenges involve internet instability, variations in parental digital literacy, data privacy concerns, and technical overload. These challenges are addressed through guidance, assistance, and service-oriented practices aligned with Islamic ethical values. The study concludes that effective digital student admission management in Islamic early childhood education requires balancing technological innovation with ethical governance, digital competence strengthening, data protection, and continuous system evaluation to ensure equitable and transparent services.